Os valores pessoais e suas influências nas políticas de gestão de pessoas: um modelo relacional de estudo em uma organização profissional mineira - Lucas Tadeu Alves Pereira (2017)
This dissertation aims to investigate the relationships between variables personal values of doctors, key professionals of the organizational structure professional bureaucracy, and policies of people management in the perception of employees. It is also sought to diagnose the situation of these variables before 313 professionals from a health organization in the city of Contagem - MG. Considering these objectives, it was decided to carry out a quantitative research and data collection was performed based on two questionnaires: one for doctors and one for non - doctors professionals (employees). The collected data were submitted to a statistical treatment that involved statistical descriptive techniques and multivariate analysis. The theoretical framework of the work consisted of the Mintzberg (2009) approach to the professional bureaucracy organizations, contemplating the health organization, Barrett's (2006) seven-level model of personal consciousness, which measured the personal values of doctors, and the approach on people management policies in the perception of employees, based on the studies of Demo (2008), in addition to the contribution of other research that refer to the authors mentioned above. The results achieved included: the validation of the proposed scales, to measure the variables of interest of the research; And the evaluation of the hypotheses that guided the work, allowing to verify the existence of a significant relationship, although of low intensity, between the variables personal values and policies of people management. The hypothesized model presented a good fit. Regarding the characteristics of the doctors, it was verified the existence of a homogeneity in relation to the levels of personal conscience. The same was true for employees, who, for the most part, did not realize that people management policies are practiced at a satisfactory or high level. In a general evaluation, it was concluded that the personal values of the doctors influence in a negative way and of low intensity the policies of people management, in the perception of the employees and that the studied organization, at the same time as it seeks to incorporate its management policies of people, does not do so through a strong participation of the key professionals of this type of organization, from the perspective of Mintzberg (2009).